2022
DOI: 10.3390/ani12151919
|View full text |Cite
|
Sign up to set email alerts
|

Plateau Adaptation Gene Analyses Reveal Transcriptomic, Proteomic, and Dual Omics Expression in the Lung Tissues of Tibetan and Yorkshire Pigs

Abstract: Elevated environments such as plateaus are often classified as low oxygen environments. The hypoxic adaptation mechanisms utilized by organisms in these conditions are not well understood. To address this, the differentially expressed genes (DEGs) involved in hypoxia adaptation were assessed using two pig breeds (Tibetan pig [TP] and Yorkshire sow [YY]). Genes related to lung tissue responses to hypoxia were assessed using transcriptomic (using RNA-seq) and proteomic (using iTRAQ) analysis. A total of 1021 DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The expression of CapG was also observed to increase in lung cancer cell lines under hypoxic conditions (Shao et al, 2011). In a screening study of candidate genes related to hypoxia adaptation, the CapG gene was found to be expressed in both Tibetan and Yorkshire pigs and enriched in regulatory pathways related to plateau hypoxia acclimatization (Shang et al, 2022).…”
mentioning
confidence: 95%
“…The expression of CapG was also observed to increase in lung cancer cell lines under hypoxic conditions (Shao et al, 2011). In a screening study of candidate genes related to hypoxia adaptation, the CapG gene was found to be expressed in both Tibetan and Yorkshire pigs and enriched in regulatory pathways related to plateau hypoxia acclimatization (Shang et al, 2022).…”
mentioning
confidence: 95%
“…1,2 In recent years, plains pig breeds such as Yorkshire pigs have been raised on a large scale in the Tibetan Plateau region to complement the rapid growth in local meat consumption. 3 In addition, captive breeding patterns and efficient feed conversion rates help to reduce the adverse effects of animal husbandry on the plateau environment. However, the adaptation and molecular mechanisms of Yorkshire pigs (plains pig breeds) to high-altitude environments have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Yorkshire pigs with low fat, high leanness, and good feeding performance are mainly used for commercial pork production. , In recent years, plains pig breeds such as Yorkshire pigs have been raised on a large scale in the Tibetan Plateau region to complement the rapid growth in local meat consumption . In addition, captive breeding patterns and efficient feed conversion rates help to reduce the adverse effects of animal husbandry on the plateau environment.…”
Section: Introductionmentioning
confidence: 99%